(untitled) (Altre Modernità, 2012)
In his discussion of Dante’s Inferno, Edward Said writes that “Maometto” or Mohammed occupies the eighth circle in the nine circles of Hell, belonging to “a rigid hierarchy of evils.” According to Said, “Maometto” is “endlessly being cleft in two from his chin to his anus,” a punishment in Dante’s belief is well deserved because of Maometto’s sensuality and “pretensions to theological eminence.” Such graphic description of torment evokes scenes of torture we have of late witnessed in Abu Ghreib and Guantanamo. Prisoners, not only, were subjected to physical abuse but were also subjected to acts of sexual perversion as was revealed by the photos. Furthermore, the latter showed those who partook in these actions seemed to be enjoying the power that the exercise of torture gave them. Robert J.C. Young states that Colonialism “was not only a machine of war … but also a desiring machine.” This poses the question as to whether torture does allow for the enactment of repressed desire by allowing it to surface by providing it with a venue in which it becomes acceptable. Moreover, does Colonialism in its previous or in its current form, only sustain itself fundamentally through constant violence, of which perversion is a vital component as these practices are playing into the repertoire of the evil East, or is the perversion an extension of a suppressed Oedipus complex?